Recent Advances in Polyurethane-Based Nanocomposites: A Review. Issue 14 (22nd September 2017) - Vaithylingam, Rajeswaran; Ansari, M. N. M.; Shanks, Robert A.
ABSTRACT: This review addresses recent advances in polyurethane-based nanocomposites. It focuses on the enhancement of mechanical, electrical, thermal, acoustic, chemical, shape memory, and viscoelastic properties of the existing polyurethane using nanoparticles or fiber materials and it is also directed to analyze the potential of incorporating these hybrid polymer composites' applications. Research on hybrid polymer composites has increased in recent years due to the inherence properties of mixing two or more constituents to reinforce the base material properties. From the discussion in this paper, we can see that polyurethane-based nanocomposite can be modified to suit various applications. GRAPHICAL ABSTRACT: